Photopolymerization of Imprinted Polymer with Dummy Template for the Recognition of Hydroquinone in Aqueous Medium - Musali, Norlin Suhaiza; Abu Bakar, Norlaili; Abdul Rahim, Nurulsaidah; Wan Mahamod, Wan Rusmawati; Hashim, Norhayati; Mohd Sharif, Sharifah Norain; Che Soh, Siti Kamilah; Ulianas, Alizar (Indonesian Journal of Chemistry, 2024)
This study' purposes are to synthesize molecularly imprinted polymer (MIP) with hydroxyethyl methacrylate (HEMA) and triethylene glycol dimethacrylate (TEGDMA) using p-xylene under ultraviolet curing at 405 nm for the recognition of hydroquinone (HQ) in aqueous medium. The template was extracted from the polymer with a mixture of methanol and acetic acid (9:1) by volume (v/v). The Fourier transform infrared (FTIR) spectrum of MIP (after wash) showed the absence of peak at the range of 840–860 cm−1, which represented the stretching outside the aromatic plane C–H at the para position (p-xylene). Field emission scanning electron microscope (FESEM) micrograph showed that the MIP had cavities compared to non-imprinted polymer (NIP). The MIP (MIP-Pxy) with ratio (monomer:crosslinker) 0.25 and 1.00% template gave the highest uptake of hydroquinone (HQ) in aqueous solution, which implied more specific recognition (highest KD value). The rebinding of HQ onto MIP-Pxy was best described by both isotherm (Langmuir and Freundlich) and kinetic model (pseudo-first and -second). The MIP was successfully synthesized using p-xylene, able to recognize HQ and was very selective to p-CP. Implication of the study, the synthesized MIP can be used for recognition and sensing materials for HQ and any similar molecules.